Evaluation of Suprasegmental or Prosodic Phonological Skills: A Classification Proposal: - Calet, Nuria; Gutiérrez-Palma, Nicolás; Jiménez-Fernández, Gracia (Revista de Investigación en Logopedia, 2025)
Suprasegmental phonological skills, or prosody, refer to the rhythmic and melodic features of language. In recent years, the study of this phonological subsystem has gained considerable interest, particularly due to evidence supporting its relationship with literacy acquisition across different languages. However, one of the main challenges in this field has been the assessment of these skills. The diversity of tasks used in research, which often evaluate different components and vary in complexity, has complicated the interpretation of results. The accumulated literature suggests that not all prosodic skill assessment tasks are comparable. Therefore, the aim of this study is to present an analysis of the key elements to consider in the assessment of prosodic skills and to propose a classification based on their characteristics and complexity. Finally, recommendations are proposed to improve the validity and comparability of prosodic assessment tasks, as well as possible directions for future research.